Efeitos do plasma frio na qualidade e nos compostos bioativos da polpa de abacate (Persea americana Mill.) - Batista, Jéssica Dayanne Ferreira (2020)
In recent years, consumption of avocado (Persea americana Mill.) has grown exponentially, as a knowledge of its nutritional characteristics and bioactive compounds, such as high concentration of unsaturated fatty acids, especially oleic acid, in addition to a variety of vitamins (A, E, B and K) and minerals such as calcium (Ca), magnesium (Mg) and phosphorus (P), which together make it be a fruit with relevant qualities, responsible for numerous health benefits, with potential antioxidant, antidiabetic, anti-hyperlipidemic, anti-obesity, bactericidal, antiviral and anti-inflammatory. Although the demand for the fruit and its derivatives has been expanding, the processing of avocado is a challenge faced by the food industry due to its intrinsic characteristics, such as high concentration of enzymes of polyphenoloxidase and peroxidase types and the high content of lipids, which provide reactions of degradation such as enzymatic browning and oxidative rancidity. Thus, the objective of this work was to evaluate the effect of cold plasma technology, through a completely randomized experimental design, in varying time (10, 20 and 30 min) and the gas flow (10, 20 and 30 mL / min ), in response to the enzymatic activity of polyphenoloxidase (PPO), the color and the content of bioactive compounds in the avocado pulp. Two avocado pulps were processed, one with the addition of 0.5% lemon extract (PACE) and the other without the addition of lemon extract (PASE). The effect of plasma on the PPO enzyme present in avocado pulps resulted in different behaviors. In PACE, a greater reduction in the enzyme activity was seen in treatments T8 and T9 (20 mL / 20 and 30 minutes) that applied greater gas flow and longer processing times. Changes in color parameters individually were also observed, however, with no noticeable changes in the coloration within the naked eye in some treatments, especially in PACE. Regarding the content of bioactive compounds, in PASE, the content of phenolic and total carotenoids increased in treatments T1 and T2 (gas flow 10 mL / 10 and 30 min) (p <0.05) and, in PACE, the highest values were found in T3 and T8 (gas flow 30 mL/10 min and 20 mL/30 min) (p <0.05) contributing to high antioxidant activity in DPPH, ORAC-H and ORAC-L assays. Cold plasma had no effect on fatty acid content in any of the analyzed avocado pulps. We conclude that the synergistic effect of lemon extract on avocado pulp (PACE) together with cold plasma technology is efficient for maintaining color, reducing the action of polyphenoloxidase and increasing the content of bioactive compounds.